Effects of three kinds of Jiuqu on the aroma components of millet Huangjiu based on HS-SPME-GC-MS - BO Tao, ZHANG Jiaojiao, LV Na, BAI Baoqing, ZHANG Jinhua, FAN Sanhong, JIA Liyan, TIAN Xiang (Zhongguo niangzao)
In order to explore the effect of different Jiuqu on the flavor of the millet Huangjiu, millet Huangjiu was brewed using three different Jiuqu (Angel Huangjiuqu, Daqu, and Hongqu), and the volatile flavor compounds in the three types of millet Huangjiu were detected by HS-SPME-GC-MS. The results showed that 235, 239, and 165 peak signals were detected in the millet Huangjiu brewed with Daqu, Hongqu, and Angel Huangjiuqu, respectively. The 32 volatile flavor compounds with high abundance identified from different Huangjiu samples were analyzed, among which 11 volatile flavor compounds were common to the three millet Huangjiu. The unique volatile flavor compounds in the millet Huangjiu brewed with Angel Huangjiuqu were heptanol, phenylacetaldehyde, and acetophenone, while the unique volatile flavor compounds in the millet Huangjiu brewed with Daqu were γ-butanone and furfural, and the unique volatile flavor compounds in the millet Huangjiu brewed with Hongqu were 2-nonone. The use of different Jiuqu had a significant impact on the flavor of millet Huangjiu, mainly reflected in the 9 different volatile flavor compounds such as isoamyl alcohol, benzaldehyde, furfural and so on which were screened by variable importance in the projection (VIP) value>1.